Development of regional tourism: factors affecting the formation of professional competence in future professionals in tourism - Otcheskiy, Ivan; Stepanova, Diana; Bitter, Natalia; Livson, Maya; Stytsyuk , Rita; Denisova, Olga (Anais Brasileiros de Estudos Turísticos, 2022)
The socio-political changes faced by Russia force universities to adjust the theoretical training and practical skills of students. These changes need to focus on the development of domestic tourism in Russia. In one hand, this brings about the need for a large number of specialists in domestic tourism and, on the other hand, for systemic adjustments to the training of future specialists in the organization of tourism. Thus, the study aims to identify factors in the formation of professional competence in future specialists in the organization of regional tourism in higher education. These factors are established through analysis of scientific sources and the results of an expert survey. We have identified to two groups of the major factors that need to be taken into consideration when training specialists. The first group of factors affects the content of training and, in particular, includes targeted formation of student motivation to master professional skills and abilities in developing regional tourist products using national experience. The second group influences the methods of training (e.g. including the use of group training methods and interactive technologies). conclusions show that he effectiveness of the formation of the professional competence of future specialists in the organization of regional tourism will be ensured primarily by targeted formation of students’ motivation to master professional skills and abilities to form a regional tourist product and the use of national experience of formation and implementation of regional tourist products in the activities of tourist enterprises. Moreover, such formation will be facilitated by the use of group teaching methods and interactive technologies in teaching the development of regional programs, as well as by opportunities to take internships in the tourism support system at national enterprises.